Macromol. Rapid Commun. 19/2014. Issue 19 (October 2014) - Takashima, Yoshinori; Sahara, Taiga; Sekine, Tomoko; Kakuta, Takahiro; Nakahata, Masaki; Otsubo, Miyuki; Kobayashi, Yuichiro; Harada, Akira
<x xml:space="preserve">Abstract</x> Front Cover: Supramolecular interactions through host‐guest interactions are used to realize adhesion between hydrogels modified by host molecules and substrates modified by guest molecules. Here, control of adhesion between hydrogels with cyclodextrin and glass substrates with stimuli responsive molecules by external stimuli is reported. This concept is adapted for bonding between materials through molecular recognition without any adhesives. Further details can be found in the article by Y. Takashima, T. Sahara, T. Sekine, T. Kakuta, M. Nakahata, M. Otsubo, Y. Kobayashi, and A. Harada* on page 1646. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>